Poddawanie się badaniom profilaktycznym przez osoby z przewlekłym wirusowym zapaleniem wątroby typu C = Submission to preventive examinations by people with chronic hepatitis C - Marta Estera Kowalska; Paweł Kalinowski; Urszula Jolanta Bojakowska (Kazimierz Wielki University, 2016)
Kowalska Marta Estera, Kalinowski Paweł, Bojakowska Urszula. Poddawanie się badaniom profilaktycznym przez osoby z przewlekłym wirusowym zapaleniem wątroby typu C = Submission to preventive examinations by people with chronic hepatitis C. Journal of Education, Health and Sport. 2016;6(7):147-153. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57298 http://ojs.ukw.edu.pl/index.php/johs/article/view/3672       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.06.2016. Revised 09.07.2016. Accepted: 09.07.2016.     Poddawanie się badaniom profilaktycznym przez osoby z przewlekłym wirusowym zapaleniem wątroby typu C Submission to preventive examinations by people with chronic hepatitis C   Marta Estera Kowalska1, Paweł Kalinowski1, Urszula Bojakowska1,2 1.      Samodzielna Pracownia Epidemiologii Uniwersytetu Medycznego w Lublinie 2.      SKN przy Samodzielnej Pracowni Epidemiologii Uniwersytetu Medycznego w Lublinie     Streszczenie Wstęp Wirusowe zapalenie wątroby typu C stanowi jeden z głównych problemów zdrowia publicznego ze względu na długi okres bezobjawowy zakażenia wirusem HCV. Cel pracy Celem pracy była analiza zachowania zdrowotnego jakim jest poddawanie się badaniom profilaktycznym przed i po wykryciu choroby osób z wirusowym zapaleniem wątroby typu C. Materiał i metody Materiałem wykorzystanym do badań były odpowiedzi na pytania zamknięte zawarte w autorskim kwestionariuszu ankiety. W badaniu wzięło udział 200 osób z potwierdzonym zakażeniem HCV. Wyniki Przed wykryciem choroby badana grupa deklarowała, że poddawała się badaniom profilaktycznym sporadycznie, jedynie gdy zaistniały niepokojące objawy.   Słowa kluczowe: wirusowe zapalenie wątroby typu C, profilaktyka.       Summary Introduction Hepatitis C is a major public health problems due to the long latency period of infection with HCV (hepatitis C virus). Aim The aim of the study was to analyze the behavior of health which is to submission to preventive tests before and after the detection of the disease people with hepatitis C. Material and methods Material used for the study were answers to closed questions included in the original questionnaire survey. The study involved 200 people with chronic hepatitis C. Results Before detection of of the disease studied group declared that they give up preventive testing occasionally, only when any worrying symptoms. Keywords: hepatitis C, prevention.